Road Repair Delay Costs in Improving the Road Rehabilitation Strategy through a Comprehensive Road User Cost Model - Ferdinand Trestanto; Sigit Pranowo Hadiwardoyo; Jachrizal Sumabrata; Riana Herlina Lumingkewas (International Journal of Engineering and Technology Innovation, 2024)
This study delves into quantifying the adverse effects of road damage on users, particularly focusing on the increased travel time and consequent financial burdens stemming from delayed repairs. Utilizing a comparative method, the research underscores notable reductions in speed and prolonged travel times due to damaged roads, leading to substantial economic losses for road users. To streamline the estimation of road user costs (RUC), the study proposes a simulation model that incorporates varying traffic volumes and repair delays. This model demonstrates a high level of accuracy in estimating RUC, revealing heightened sensitivity to fluctuations in traffic volume and repair delays compared to agency costs. Consequently, the research underscores the imperative of implementing effective repair strategies to alleviate these impacts efficiently, thereby emphasizing the significance of timely infrastructure maintenance in mitigating financial burdens on road users.